Perovskite Materials for Light‐Emitting Diodes and Lasers. Issue 32 (23rd May 2016) - Veldhuis, Sjoerd A.; Boix, Pablo P.; Yantara, Natalia; Li, Mingjie; Sum, Tze Chien; Mathews, Nripan; Mhaisalkar, Subodh G.
Abstract : Organic–inorganic hybrid perovskites have cemented their position as an exceptional class of optoelectronic materials thanks to record photovoltaic efficiencies of 22.1%, as well as promising demonstrations of light‐emitting diodes, lasers, and light‐emitting transistors. Perovskite materials with photoluminescence quantum yields close to 100% and perovskite light‐emitting diodes with external quantum efficiencies of 8% and current efficiencies of 43 cd A −1 have been achieved. Although perovskite light‐emitting devices are yet to become industrially relevant, in merely two years these devices have achieved the brightness and efficiencies that organic light‐emitting diodes accomplished in two decades. Further advances will rely decisively on the multitude of compositional, structural variants that enable the formation of lower‐dimensionality layered and three‐dimensional perovskites, nanostructures, charge‐transport materials, and device processing with architectural innovations. Here, the rapid advancements in perovskite light‐emitting devices and lasers are reviewed. The key challenges in materials development, device fabrication, operational stability are addressed, and an outlook is presented that will address market viability of perovskite light‐emitting devices. Abstract : Perovskites have sparked a revolution in photovoltaics, and their excellent optoelectronic properties hold the potential to trigger a similar advance in the field of light emission. The versatility of organic–inorganic hybrid perovskites as emitters and gain media is explored, device performance/architectures, processing conditions, and working mechanisms are analyzed, and the main barriers toward market viability are addressed.